A metal nanoparticle assembly with broadband absorption and suppressed thermal radiation for enhanced solar steam generation. Issue 18 (26th April 2021) - Ding, Dawei; Wu, Hu; He, Xiaoping; Yang, Fan; Gao, Chuanbo; Yin, Yadong; Ding, Shujiang
Abstract : The efficiency of solar steam generation is boosted by broadband solar absorption and suppressed thermal radiation loss of a nickel-nanoparticle-based spectrally selective absorber. Abstract : Solar steam generation is an attractive technology for harvesting solar energy. Many efforts have been devoted to developing absorbers with increased solar energy absorption efficiency. However, little attention has been paid to the thermal radiation loss of the absorbers, which is equally important for achieving high solar-steam efficiency. To address this issue, herein, we report a solar harvesting strategy by introducing a nickel-nanoparticle-based spectrally selective absorber that possesses high and broadband absorption in the solar irradiation region but minimal thermal emittance at long-infrared wavelengths. Nickel nanoparticles are encapsulated in silica and carbon nanoshells, which are then assembled in an orderly manner on an infrared reflector to form a harvesting structure of graded refractive indices. As a result, high solar absorptance ( α ≈ 0.93) but low thermal emittance ( ε ≈ 0.096) has been achieved. An interfacial evaporation system with this unique absorber demonstrates a boosted water evaporation rate of 1.52 kg m −2 h −1 under 1 sun, which is ∼5 times the value for water alone, making it one of the best absorbers for solar steam generation applications. The combined advantages of high efficiency and durability suggest its potential for industrial water purification and desalination applications.